Multiple performance pressure inconsistency, resource slack, and the firm's R&D investment: A behavioral agency theory perspective - David Diwei Lv; Weihong Chen; Hailin Lan (BRQ Business Research Quarterly, 2022)
In the process of operation, firms will face different types of performance pressure. The inconsistency among multiple performance pressure signals has an important impact on resource allocation and R&D investment. However, at present, studies on the impact of multiple performance pressures on the firm's resource allocation and R&D investment are very limited, and few studies have analyzed the impact of inconsistencies among multiple performance pressure signals on the firm's R&D investment. Given this research gap, this article empirically tested a model from the perspective of behavioral agency theory, in which inconsistency in long- and short-term performance pressure facilitates the accumulation of organizational slack. We further test the impact of an increase in organizational slack on the firms' R&D investment intensity and find that this effect is stronger when the level of managerial ownership is comparatively low. These results together indicate that high inconsistency in performance pressure and low managerial ownership jointly facilitate the accumulation of organizational slack, enabling firms to go beyond local search and have more slack searches in the face of multiple performance pressure, which is conducive to an increase in R&D investment.
Keywords: M10; 650; Multiple performance pressure; inconsistency; R&D investment; behavioral agency theory; organizational slack